Bio‐inspired Dynamic Gradients Regulated by Supramolecular Bindings in Receptor‐Embedded Hydrogel Matrices. Issue 4 (30th June 2016) - Luan, Xinglong; Zhang, Yihe; Wu, Jing; Jonkheijm, Pascal; Li, Guangtao; Jiang, Lei; Huskens, Jurriaan; An, Qi
Abstract: The kinetics of supramolecular bindings are fundamentally important for molecular motions and spatial–temporal distributions in biological systems, but have rarely been employed in preparing artificial materials. This report proposes a bio‐inspired concept to regulate dynamic gradients through the coupled supramolecular binding and diffusion process in receptor‐embedded hydrogel matrices. A new type of hydrogel that uses cyclodextrin (CD) as both the gelling moiety and the receptors is prepared as the diffusion matrices. The diffusible guest, 4‐aminoazobenzene, quickly and reversibly binds to matrices‐bound CD during diffusion and generates steeper gradients than regular diffusion. Weakened bindings induced through UV irradiation extend the gradients. Combined with numerical simulation, these results indicate that the coupled binding–diffusion could be viewed as slowed diffusion, regulated jointly by the binding constant and the equilibrium receptor concentrations, and gradients within a bio‐relevant extent of 4 mm are preserved up to 90 h. This report should inspire design strategies of biomedical or cell‐culturing materials. Abstract : Dynamic gradients : The kinetics of supramolecular bindings is employed in a diffusion process to regulate molecular spatial–temporal distributions. The diffusible guest, 4‐aminoazobenzene, quickly and reversibly binds to matrices‐bound cyclodextrin during diffusion and generates steeper gradients than regular diffusion. Weakened bindings induced by UV irradiation extend the gradients. A gradient within 4 mm could be preserved for up to 90 h through the coupled "binding–diffusion" process.